2012
DOI: 10.1111/j.1365-2621.2012.03017.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of non‐GMO biofortified pearl millet (Pennisetum glaucum) for increasing iron and zinc content and their estimated bioavailability during abrasive decortication

Abstract: Summary Two non‐GMO biofortified and one traditional pearl millet varieties were compared in abrasive decortication studies to evaluate their potential for increasing iron and zinc content. The phytate‐to‐mineral ratios were used to estimate mineral bioavailability. Iron and zinc contents in the biofortified varieties Tabi and GB8735 were two to threefold higher than in the traditional variety. Iron content reached 7.2 and 6.7 mg per 100 g DM in the biofortified varieties, which corresponds to the target value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
3
21
1
Order By: Relevance
“…The extent of variation in the Fe, Zn and Al concentrations observed is presented in . These ranges were substantially narrower than those recently reported for pearl millet (Hama et al, 2012;Rai et al, 2013;Bashir et al, 2014;Pucher et al, 2014), perhaps because the tested materials did not include any Iniari landrace-derivatives. Based on their mean performances across the four environments, the varieties ICRI-Tabi and ICMV-IS 13131 (reselected ICRI-Tabi) were identified as stable and more promising for grain Fe density.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The extent of variation in the Fe, Zn and Al concentrations observed is presented in . These ranges were substantially narrower than those recently reported for pearl millet (Hama et al, 2012;Rai et al, 2013;Bashir et al, 2014;Pucher et al, 2014), perhaps because the tested materials did not include any Iniari landrace-derivatives. Based on their mean performances across the four environments, the varieties ICRI-Tabi and ICMV-IS 13131 (reselected ICRI-Tabi) were identified as stable and more promising for grain Fe density.…”
Section: Resultscontrasting
confidence: 54%
“…Development of pearl millet varieties with high grain density and/or availability of Fe and/or Zn could contribute to the reduction of Fe and Zn deficiencies in millet-dependent populations in WCA (Hama et al, 2012;Pucher et al, 2014). Therefore, the objective of this study was to assess the genetic variability of Fe, Zn, Al and P grain concentrations among 12 pearl millet farmerpreferred varieties tested across representative sites in Niger.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported higher concentrations up to 20 mg iron/100 g pearl millet (1416); however, such concentrations most likely include contaminant iron from post-harvest treatments and should not be used for reporting native iron concentration of pearl millet (17). The iron concentration of iron-biofortified pearl millet has been reported to be ∼7–8 mg/100 g (18, 19), which is about double the iron content of other major cereal staples. Compared with regular pearl millet, the iron-biofortified varieties usually also have higher phytic acid (PA) concentrations (18).…”
Section: Introductionmentioning
confidence: 99%
“…Bioefficacy studies on biofortified crops is a clear evidence for the antagonistic effect of IP 6 on mineral absorption. Hama et al (2012) carried out bioefficacy studies of biofortified and traditional pearl millet varieties of Africa subjected to abrasive decortication. Iron content of biofortified varieties (Tabi and GB8735) was 72 and 67 mg/kg dry matter, respectively.…”
Section: Antinutrientsmentioning
confidence: 99%